Comprehensive DFT analysis of BeHfO3 perovskite: Exploring the structure, mechanical, thermodynamic, and optic properties - Al Masud, Md; Munshi, Md. Rajib; Chowdhury, Tanvir; Chakraborty, Mita; Islam, Rakibul (European Journal of Chemistry, 2025)
We performed a thorough study of the electronic, mechanical, thermodynamic, and optical properties of the BeHfO3 perovskite crystal using first-principles calculations featuring density functional theory (DFT). Electronic band structure analysis manifested the material to be semiconducting in nature with calculated band gap values of 0.873 eV (PBE), 0.887 eV (RPBE), 0.781 eV (PBEsol), 0.890 eV (LDA), 1.71 eV (HSE06) and 2.925 eV (B3LYP), reflecting considerable uncertainty in terms of exchange-correlation functionals and emphasizing the utility of hybrid functionals in estimating the band gap. Density of states (DOS) and partial density of states (PDOS) analyses were vital in revealing the role of the participating atoms (Be, Hf, and O) in electronic contribution, orbital hybridization, and the major states close to the Fermi level, highlighting the dominant states near the Fermi level and the role played by them in bonding. The Mulliken population analysis also described the electrostatic interaction and charge reorganization, confirming the mixed ionic-covalent nature of the bonds and revealing the complexity in the nature of bonds in the BeHfO3 lattice. Mechanical stability was thoroughly analyzed using the Born mechanical stability criteria (BMS) which validated the mechanical stability of the compound. The calculation of the elastic constants helped to establish Poisson’s ratio and Pugh’s modulus ratio (B/G) to confirm the mechanical strength and ductility of the compound along with the pronounced anisotropy in the elastic properties, which could be valuable in applications requiring directional devices. The calculation of the optical properties in terms of the frequency-dependent dielectric functions and the absorption coefficients using different DFT approaches proved the material to be a powerful absorber in both the ultraviolet (UV) and visible parts of the spectrum, which establishes the material as a valuable contender in the field of optoelectronic and photocatalytic technology.